RANCANG BANGUN APLIKASI PEMINJAMAN BUKU UNTUK MENINGKATKAN MANAJEMAN PELAYANAN PERPUSTAKAAN DI SMP 1 ABUNG TENGAH LAMPUNG UTARA - Erjon, Erjon; Widi, Dewi; Ameliya, Riski Putri (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2019)
The rapid development of science and technology today has an effect on progress in the education sector. One of the important elements to be a school that can print a good student is to improve the school library services are complete and supported by good library data administration. This continues to be accompanied by a careful, precise and fast management and information system. The purpose of this research is to make school library loan application system especially in SMP1 Abung Tengah by using Visual Basic. 6.0 and Microsoft Access 2007 to overcome the problem of administration of school libraries that have been done semi-computer. This system is designed to facilitate administration of school libraries that include member data, book data, borrowing data and return data. With the system is expected to data processing can be faster, precise and efficient. So that services to learners can be better which will impact on improving the quality of education in SMP 1Abung Tengah in particular and in Indonesia in general.